Juventude e políticas sociais no Brasil - Jorge Abrah\~ao de Castro; Luseni Aquino (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This document presents a review on how youth issues have been dealt with in the field of social policies in Brazil. The first paper proposes an extensive approach to the theme by revising the main concepts of youth that have given shape to public policies and pointing out some of the crucial issues related to young people in Brazil nowadays. The next ten papers analyze federal social policies in relation to youth (education, labour, health, social care, culure, public security etc.). The aim here is to evaluate how adequate they have been to the problems that actually concern young Brazilians. Finally the last paper examines the National Youth Policy since 2005 and indicates some of its main achievements and great dilemmas.
Keywords: I38; J13; Z13; 330; Jugendliche; Sozialpolitik; Brasilien